Drug-Resistant Epilepsy in Pediatric Patients: Current Evidence on the Therapeutic Role of Ketogenic Diet - Jopek, Jakub; Tymchenko, Hanna; Świątecka, Martyna; Kaźmierczyk, Jakub; Bryksy, Sylwia; Popczyk, Natalia; Przybyłowska, Agnieszka; Buczkowska, Ewa; Marciszewska, Aleksandra; Popczyk, Michał (Quality in Sport, 2025)
Background: Epilepsy affects millions worldwide, and approximately one-third of patients develop drug-resistant epilepsy, particularly burdensome in pediatric populations, where comorbid developmental impairments are common and underlying mechanisms remain only partially defined. Emerging evidence indicates that non-pharmacological approaches - most notably modern, better-tolerated ketogenic dietary variants - can reduce seizure burden by including therapeutic ketosis and shifting cerebral energy toward ketone body utilization. Materials and methods: An extensive literature review was conducted using sources retrieved from the PubMed and Google Scholar databases. Aim: The aim of this study was to analyze and synthesize current knowledge and drug-resistant epilepsy in children, as well as to evaluate the role of non-pharmacological interventions, specifically the classical ketogenic diet and its alternative formulations (MAD, LGIT). Conclusions: The classical ketogenic diet (cKD) is effective in children with drug-resistant epilepsy (DRE), but its strict regimen and poor palatability often limit adherence. Alternative approaches, such as the modified Atkins diet (MAD) and low glycemic index treatment (LGIT), are better tolerated and more flexible, though slightly less effective. Further research is needed to clarify underlying mechanisms and optimize dietary therapies for DRE.